Pengelolaan Pengaduan Gangguan Internet Pelanggan Indihome Pada Plasa Telkom Witel Makassar - Hakim, Fadil; Haerana, Haerana; Wahid, Nur (Universitas Muhammadiyah Makassar, 2022)
The purpose of this study is to describe and explain the Management of Internet Interference Complaints by Indihome Customers at Plasa Telkom Witel Makassar. The type of research used is a qualitative research method, the type of descriptive research. Data collection techniques using observation, interviews and documentation. The results of the study show 3 (three) implementation processes in the Management of Internet Interference Complaints for Indihome Customers at Plasa Telkom Witel Makassar, namely: (1). The management of complaints of internet disturbances to customers of indihome Plasa Telkom Witel Makassar has been said to be very good in overcoming various problems experienced by customers. (2). The supporting factors in the telkom witel makassar plaza in managing internet disturbance complaints have been said to be good in repairing internet disturbance complaints, because the facilities at the telkom witel makassar plaza are complete in fixing a problem that occurs on the internet network. (3). The inhibiting factor in the plasa telkom witel Makassar in managing internet disturbance complaints is not yet good because the materials commonly used in repairing internet disturbances.Keywords: Management System, Supporting Factors and Inhibiting Factors